GERAKAN LITERASI DALAM MENINGKATKAN MINAT BACA MASYARAKAT MELALUI PERAN PERPUSTAKAAN DAN PUSTAKAWAN - fepi febianti (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2021)
Interest in reading is the emergence of feelings of pleasure or strong interest that encourages individuals to carry out activities so that they do it on their own accord. Then there are attempts to do this activity repeatedly. reading is an important activity. Human civilization will not be far from this activity. Even in its history, a civilization is said to be advanced if humans at that time had the ability to read and write. Even in Islam, the first commandment to the Prophet Muhammad was to read (iqra`: read). It has also been proven, a nation with a high interest in reading becomes a nation that excels in science and technology. By reading, you can find a variety of knowledge and make discoveries in both the scientific and social fields. Based on research on reading interest, broadly speaking, there are two factors, namely internal and external factors. Internal factors generally include perceptions, motivations, and individual feelings towards reading activities. Meanwhile, external factors relate to the environment, ease of access to books, availability of facilities and infrastructure, technological developments, and even distribution of reading books. Therefore, a unique literacy is needed to support the reading culture of the community. Literacy has an important role in the life of a learning community that lives in an era that is based on current knowledge, technology, and information. Human civilization can be awakened by mastery of literacy based on reading, writing, and critical thinking activities. Literacy is a process of how a person communicates in society. In addition, literacy can also be interpreted as practice and social relations related to knowledge, language, and culture. Libraries with librarians can be used to develop a literacy culture for users in particular and society in general. With the available resources, together with stakeholders and community groups, they can innovate, create, and vary literacy-based library services. Thus the literacy culture will grow and develop.